Basic biology and clinical impact of immunosenescence - Pawelec, G. (Graham) (Advances in cell aging and gerontology, 2003)
Ageing is of perennial interest as a universal feature in all human societies. The genetic background and biochemical bases of ageing processes are currently being revealed in unprecedented detail. It is emerging that one of the main hurdles to be overcome in achieving a long and healthy lifespan is the maintenance of a properly functioning immune system. The main cause of death in people who have achieved "successful ageing" (which mostly means not having succumbed to cancer or cardiovascular disease) is infectious disease, caused by immunosenescence. This book contains chapters by many of the leaders in the field of immune-related issues in ageing and remediation